Social Justice and Gender Relations in the Shaping of Cultural Identity and Collective History - Puspita, Melati; Aprilia, Cika; Aditya, Dimas (Journal Social Humanity Perspective, 2024)
This research paper discusses the ways in which social justice meets gender relations in creating cultural identity and shared history and how they apply to management and organization studies. Using a qualitative methodology, the current study examines the role of narratives about gendered experience in the context of justice and the effect of such narrations on the collective memory and cultural negotiation. Taking the form of pseudo-empirical in-depth interviews and document research, data were collected in a way that would allow researchers to analyze lived experiences as places where historical inequities and cultural identities are constantly created and recreated. The results demonstrate that the narratives on gendered stories play an important role in conceptualizing collective memory, whereas social justice has become a continuous cultural conflict within the institutional and communal activities. In addition, the paper demonstrates that negotiations of cultural identity and gender can become transformative processes ensuring new inclusion and recognition within organizations and society. To the management, the paper postulates that organizations are inseparable in the general cultural and historical processes which influence their institutions and values, leadership styles and policy orientations. Integration of egalitarian principles, somatization with gender and cultural sensitivity are not only an ethical role, but a business imperative to legitimacy and sustainability. The study addresses the role of social justice and gender relations in explaining organizational culture to facilitate the development of more inclusive modes of management capable of embracing the dynamics of cultural identity and historical memory.